Beneficial Effects of Monascus sp. KCCM 10093 Pigments and Derivatives: A Mini Review - Kim, Daehwan (Molecules, 2018)
The production of Monascus pigments and related byproducts, via microbial fermentation, has been broadly utilized as coloring by traditional food industries and as a natural textile dye. In addition to these traditional purposes, Monascus pigments have been recently favored for a variety of commercial and academic purposes. Pigments and derivatives formed during Monascus fermentation have pharmaceutical and clinical properties that can counteract common diseases, including obesity, type-2 diabetes, and cancer. Various research attempts have investigated the optimum conditions for this derived compound synthesis, as well as the still-unknown bio-functional effects. Recently, several studies were conducted using Monascus sp. KCCM 10093 and its derivatives. These experimental outcomes potentially reflect the bio-functional features of Monascus sp. KCCM 10093. However, no publication to date provides an overview of Monascus sp. KCCM 10093’s unique metabolite products, functionalities, or biological pathways. In order to develop profitable commercial applications of Monascus sp. KCCM 10093, it is necessary not only to conduct continuous research, but also to systematically organize previous Monascus studies. The goals of this review are to investigate the current derivatives of Monascus sp. KCCM 10093 pigments—some of which have demonstrated newly-identified functionality—and the relevant uses of these molecules for pharmaceutical or nutraceutical purposes.